Health status of a group of cellulose industry workers - Maria Elisa Gonzalez Manso (O Mundo da Saúde)
Healthy workplace, according to the World Health Organization, is one in which workers and managers collaborate in a process of continuous improvement in order to protect and promote health, safety and welfare of all employees and sustainability of the environment. This article is a part of a program which has been implemented by a company linked to a papermaking industry, specifically in the biological domain and aiming at health promotion. It presents the results obtained by a “screening” performed both in industrial plants in the Southeast and in the Northern region, pointing to the differences found. In this case, we highlight the challenges, not only in deploying the programs themselves, but those coming from so diverse cultural, social and epidemiological realities.